DOI: HTTPS://DOI.ORG/10.36873/AE , FIRLIANTY, HERMANSYAH, RARIO, ELITA, WINDARINA SAMOSIR: KAJIAN EFEKTIVITAS EKSTRAK GEL IKAN TOMAN (CHANNA MICROPELTES) PADA LUKA BAKAR MENCIT (MUS MUSCULUS) - Agrienvi (Agrienvi, Jurnal Ilmu Pertanian, 2019)
ABSTRACTThis study aims to know the effectivity of snakehead (Channa micropeltes) gel extract on the burns healing ofrat (Mus musculus). It was carried out for 4 months, September 2018 to January 2019. The study employed anexperimental method of Complete Randomized Design with 4 treatmnets and 3 replications. Treatment A was control,B used 1.5% gel extract of C. micropeltes, C used 3 %, and D used 4.5%, respectively. Results revealed that in day4, 8 and 12 the administration of gel extract of C. micropeltes gave significant effect on the burns healing of rat (Musmusculus) (Fcalc.> Ftab., 0.05).Keywords : gel extract, Channa micropeltes, rat Mus musculus, burns healing.